Ultrafast reaction‐sintering of grain size‐controlled titanium niobate from TiO2 and Nb2O5 - Vinícius S. G. Oliveira (Wiley, 2021)
Abstract TiNb2O7 is a promising alternative to graphite anodes currently employed in lithium‐ion batteries. The material offers a high specific capacity, good cycling stability, and better safety characteristics. The solid‐state reaction between TiO2 and Nb2O5 is the most straightforward synthesis route to prepare TiNb2O7. It has only been documented so far to be conducted at long periods of sintering time (>10 h). In this work, we propose a fast‐firing approach to the solid‐state synthesis, which yields TiNb2O7 in less than 2 min of furnace holding time, starting from tape‐cast titania (d50 = 0.26 μm) and niobia (d50 = 0.967 μm) green compacts. Besides significantly reducing processing time, fast‐firing enabled the hindering of grain growth, producing a material with grain size ∼0.5 μm (holding time of 2 min) and ∼1 μm (5–10 min).